2021
DOI: 10.1001/jamadermatol.2020.4372
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Proposed New Staging System for Folliculotropic Mycosis Fungoides With Prognostic Variables in a US Cohort

Abstract: IMPORTANCE A new cutaneous staging system for folliculotropic mycosis fungoides (FMF) has been purported to better estimate survival compared with the staging system for conventional mycosis fungoides.OBJECTIVE To analyze predictive variables associated with survival and evaluate the effectiveness of the newly proposed staging system for estimating overall survival and disease-specific survival (DSS) in a US cohort. DESIGN, SETTING, AND PARTICIPANTSThis cohort study assessed 195 patients with FMF in the dermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
(63 reference statements)
1
8
0
2
Order By: Relevance
“…A recently published study from the United States found that the cutaneous stage was only the significant parameter for predicting DSS. This study also confirmed that FMF is a heterogenous disease divided into early and advanced stages, and poorer prognosis is associated with advanced cutaneous stage 54 …”
Section: Folliculotropic Mycosis Fungoides and Prognosissupporting
confidence: 79%
“…A recently published study from the United States found that the cutaneous stage was only the significant parameter for predicting DSS. This study also confirmed that FMF is a heterogenous disease divided into early and advanced stages, and poorer prognosis is associated with advanced cutaneous stage 54 …”
Section: Folliculotropic Mycosis Fungoides and Prognosissupporting
confidence: 79%
“…Patients with low‐risk (0–1 risk factors) disease experienced superior 5‐year OS (68%) compared with the 5‐year OS observed (28%) among those with high‐risk (3–4 risk factors) disease 11,106–110 . An alternative staging system has been proposed for those with folliculotropic MF and identifies a subset of patients with limited cutaneous involvement and a more favorable prognosis 111,112 . Given the importance of the TNMB classification in risk‐stratification and defining disease burden, the ISCL/EORTC recommends its use in defining the initial, maximum and current burden of disease, which will ultimately play an important role in the selection of either skin‐directed or systemic therapies 93 .…”
Section: Risk‐stratificationmentioning
confidence: 99%
“…However, newer studies have shown that FMF patients can be subdivided into two clinical groups, an early indolent group of patients with follicle‐based patches, flat plaques, keratosis pilaris like and acneiform lesions and an advanced stage group of patients having thick follicle‐based infiltrated plaques and tumors. The latter group is less responsive to therapies and carries a worse prognosis [2931, 34, 35].…”
Section: Mycosis Fungoidesmentioning
confidence: 99%